Dopingprävention: Eine soziologische Expertise - Thiel, Ansgar; Bette, Karl-Heinrich; Kühnle, Felix (transcript, 2014)
Organised sport has so far made numerous attempts to combat doping not only through controls but also through prevention. This book offers the first sociological study in which the possibilities and limits of preventive measures in top-class sport are explored critically and constructively. The authors analyse the mechanisms that repeatedly generate doping behind the backs of the players and, on the basis of this knowledge, examine the most important prevention initiatives in German sport. Concrete recommendations on how the doping problem could be dealt with in the future make the volume interesting not only for sports sociologists and scientists but also for officials and athletes.